Integral field spectroscopy with SINFONI of VVDS galaxies - Epinat, B.; Contini, T.; Le Fèvre, O.; Vergani, D.; Garilli, B.; Amram, P.; Queyrel, J.; Tasca, L.; Tresse, L. (Astronomy and astrophysics (Berlin), 2009)
Context. Identifying the main processes of galaxy assembly at high redshifts is still a major issue in understanding galaxy formation and evolution at early epochs in the history of the Universe. Aims. This work aims to provide a first insight into the dynamics and mass assembly of galaxies at redshifts $1.2 < z < 1.6$, the early epoch just before the sharp decrease of the cosmic star formation rate. Methods. We use the near-infrared integral field spectrograph SINFONI on the ESO-VLT under 0.65´´ seeing to obtain spatially resolved spectroscopy on nine emission line galaxies with $1.2 ≤ z ≤ 1.6$ from the VIMOS VLT Deep Survey. We derive the velocity fields and velocity dispersions on kpc scales using the Hα emission line. Results. Out of the nine star-forming galaxies, we find that galaxies are distributed in three groups: two galaxies can be well reproduced by a rotating disk, three systems can be classified as major mergers and four galaxies show disturbed dynamics and high velocity dispersion. We argue that there is evidence for hierarchical mass assembly from major merging, with most massive galaxies with $M>10^{11}~{M_\odot}$ subject to at least one major merger over a 3 Gyr period as well as for continuous accretion feeding strong star formation. Conclusions. These results point towards a galaxy formation and assembly scenario which involves several processes, possibly acting in parallel, with major mergers and continuous gas accretion playing a major role. Well controlled samples representative of the bulk of the galaxy population at this key cosmic time are necessary to make further progress.